IDENTIFIKASI DAN PREVALENSI EKTOPARASIT PADA KEPITING BAKAU (SCYLLA SERRATA) DI TAMBAK DESA BAGAN PERCUT UJUNG KECAMATAN PERCUT SEI TUAN DAN TAMBAK KELURAHAN TANGKAHAN LAGAN BARAT KECAMATAN SEI LEPAN - Nanda Putri; Dwi Suryanto; Ahmad Muhtadi (AQUACOASTMARINE, 2018)
The infectious of ectoparasites has a harmful impact to mangrove crabs. This study aimed to know ectoparasites that infected mangrove crabs and determine the prevalence of ectoparasites that attack mud crabs. 10 crabs / pond were randomly taken from two pounds. Identification of Crab was conducted in Laboratory of Water Resource Management, Faculty of Agriculture, University of Sumatera Utara. Parasite were observed in walking foot, swimming foot, claws, carapaks and gill of the crab. The result showed that 4 ectoparasites i.e Vorticella, Epistylis, Zoothamnium and Octolasmis were found from crabs of two ponds. Vorticella, Epistylis, and Octolasmis of Bagan Percut Ujung showed a relative high prevalence of 50%, while Octolasmis of Tangkahan Lagan Showed high Prevalence of 30%.Keywords: Ectoparasit, Mangrove Crab, Prevalence